Handbook of effective inclusive schools : research and practice - McLeskey, James, 1949- (New York : Routledge, 2014)
'Over the last decade, the educational context for students with disabilities has significantly changed primarily as a result of mandates contained in NCLB and IDEA. The purpose of this book is to summarize the research literature regarding how students might be provided classrooms and schools that are both inclusive and effective. Inclusive schools are defined as places where students with disabilities are valued and active participants in academic and social activities and are given supports that help them succeed. Effectiveness is addressed within the current movement toward multi-tiered systems of support and evidence-based practices that meet the demands of high-stakes accountability'--
Organizational and systemic perspectives on effective inclusive schools -- Effective inclusive schools for students with high incidence disabilities -- Effective inclusive schools for students with severe disabilities -- Supporting effective inclusive schools : emerging trends and future directions.
Includes bibliographical references and index.
Keywords: Inclusive education -- United States; Special education -- United States; Children with disabilities -- Education -- United States; Mainstreaming in education -- United States